Tetracycline-inducible gene expression system in Leishmania mexicana - Kraeva, Natalya; Ishemgulova, Aygul; Lukeš, Julius; Yurchenko, Vyacheslav (Molecular and biochemical parasitology, 2014)
Here we present a T7-driven, tetracycline-inducible system for protein expression in human pathogen Leishmania mexicana. The gene expression in this strain is tightly regulated and dose- and time-dependent. This system can be widely used by the parasitology community to analyze effects of genes of interest on biology, physiology and virulence of parasites causing cutaneous leishmaniases.
Keywords: tetracyklin; Tet-inducible system; Tetracycline; Gene expression; exprese genu; Humans; Leishmaniasis, Cutaneous; leishmanióza kožní; Leishmania mexicana; lidé; Gene Expression; protozoální proteiny; Protozoan Proteins